Ransom - Steel, Danielle (London Corgi Books, 2005)
Fernanda Barnes' life was once graced by security, success and stunning wealth. Now, widowed and with a mounting pile of debts, she is trying desperately to shield her three children from the rising panic within her.
English Fiction.
Keywords: Ex-convicts -- California--San Francisco -- Police